Autonomous articulations of creative practices and resources management in art production and exhibition in Rio de Janeiro - Frechette, Alex (Brazilian Journal of Operations & Production Management, 2018)
This paper presents some strategies on the productive inclusion of visual and literary arts in an attempt to contribute to the debate concerning Creative Economy’s relationships against the neoliberal landscape in which the culture market is embedded. For this purpose, we have initially used some examples of actions taken by Brazilian and foreign artists, sensibly shifting towards the social-political context of artivism, until we reach the management of personal experiences.